Building MAGIC populations : Novel resources for sunflower trait improvement - Dominguez, Matías; Colombo, Denis Nahuel; Filippi, Carla Valeria; Ben Guerrero, Emiliano; Dillchneider Loza, Alexandra; Corro Molas, Andres Ezequiel; Montecchia, Juan Francisco; Fass, Monica Irina; Lavandera, Javier Eduardo; Troglia, Carolina Beatriz; Lia, Veronica Viviana; Gonzalez, Julio Horacio; et al. (Elsevier, 2025)
Multiparent advanced generation inter-cross (MAGIC) populations improve the accuracy of quantitative trait loci mapping compared to biparental populations by increasing diversity and reducing linkage disequilibrium between variants. Here we describe the development of two MAGIC populations derived from a cross of 11 founder lines from the INTA (National Institute for Agricultural Technology in Argentina) sunflower breeding program. The founder lines are fertility maintainer inbred lines that exhibit genetic diversity in several traits, including flowering cycle, plant architecture, disease resistance, oil content and oil quality. The crossing scheme applied follows the design of two-way, four-way and eight-way crosses with a modification to increase the number of recombinations and shorten the linkage disequilibrium. Phenotyping a subset of F2 families and F5 lines for different traits shows an increase in the diversity of the analyzed traits compared to the parental lines. In addition, we identified lines with transgressive segregation for Sunflower Verticillium Wilt resistance. These results confirm that the MAGIC populations will serve as unique genetic and genomic resources to better characterize the genetics of complex traits and identify potentially superior alleles for sunflower breeding. It will also enrich the gene pool of fertility maintainers (A/B line) of the sunflower germplasm and facilitate the introduction of new breeding methods to select female parents for use in AxR combinations to obtain superior sunflower hybrids.